Designing Healthy Blue Spaces: Principles, Patterns, and Methods for Freshwater Blue Space Design in Urban Environments - Zhang, Haoxiang (A+BE | Architecture and the Built Environment, 2025)
This thesis investigates the practical connection between health-promoting evidence and the spatial design of blue spaces. This endeavour aims to develop instrumental resources that facilitate the integration of the health benefits of natural environments into actionable strategies, thereby augmenting the development of design research and enhancing understanding of the nature-health nexus. The research methodically examines three interrelated aspects: understanding the academic contexts and methodological preparation from the design perspective, development of qualitative and quantitative design knowledge for fulfilling health benefits of blue spaces, and applications and reflections on proposed knowledge through design workshops and interviews. Initially, the thesis outlines the relationship between blue space and health from a design perspective, identifying a significant, unexplored gap. It then proposes a methodological framework to translate health-promoting evidence of blue spaces into design knowledge for practices. Subsequently, this thesis employs interdisciplinary techniques, integrating both qualitative and quantitative approaches, to generate varied types of design knowledge, including distilling worldwide precedent cases, summarising diverse geospatial and visualisation tools, and translating site-based evidence using spatiotemporal crowdsourcing data. The effectiveness and usability of the proposed knowledge are evaluated through design workshops, complemented by expert interviews across various fields, providing insights that reflect on the research outcomes and suggest future directions. Overall, by focusing on the interactive relationship between research and design, the principal contribution of this research lies in its attempt to translate theoretical evidence from public health into practical design interventions, exploring the potential of interdisciplinary tools and methods in facilitating this process.